DETERMINASI TAX AVOIDANCE PADA INDUSTRI PERTAMBANGAN: BUKTI EMPIRIS DARI INDONESIA - Lysa Myselly Vera; Nurul Aisyah Rachmawati (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2025)
This study aims to examine the influence of profitability, the corporate income tax rate, firm size, and independent commissioners on tax avoidance. The population in this research consists of mining sector companies listed on the Indonesia Stock Exchange (IDX) during 2018–2021. The sampling technique used is purposive sampling, resulting in a total of 82 research samples. This study employs secondary data derived from the companies' financial statements published on the official IDX website. The panel data analysis results demonstrate that profitability has a positive and significant effect on tax avoidance. Meanwhile, the corporate income tax rate has a negative and significant effect on tax avoidance. Conversely, firm size and the proportion of independent commissioners do not have a significant effect on tax avoidance.